ANALISIS PENGARUH KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUASAN KONSUMEN - Hasan Abdullah (Yayasan Nusantara Hasana Berdikari, 2025)
This research aims to find out how much influence product quality and service quality have on consumer satisfaction. The population in this study were customers of Cv.GenArt Advertising Banyuwangi with a sample size of 100 respondents and the technique used was nonprobability sampling. Data collection uses questionnaires that have been filled in by consumers. And data analysis techniques use validity tests, reliability tests, multiple linear regression analysis, hypothesis testing via the f test and t test, as well as the coefficient of determination (R2). Data processing in this research uses SPSS Statistics 25. The results of this research show that partially there is a positive and significant influence between product quality and consumer satisfaction as shown by the t count of 6.236. There is a positive and significant influence between service quality on consumer satisfaction as shown by the t count of 6.726. There is a significant influence between product quality and service quality simultaneously on consumer satisfaction, this is shown by the calculated F value of 36.591. Based on the coefficient of determination (R2), it shows that the contribution of product quality and service quality has an effect on consumer satisfaction of 0.410, which means that 41% of consumer satisfaction can be explained by independent variables consisting of: product quality and service quality, and the remaining 59% is explained by variables others not included in this study.